The mid-term effect of Osgood-Schlatter disease on knee function in young players from elite soccer academies - Bezuglov, E.; Pirmakhanov, B.; Ussatayeva, G.; Emanov, A.; Valova, Y.; Kletsovskiy, A.; Khaitin, V.; Usmanova, E.; Butovskiy, M.; Morgans, R. (The Physician and Sportsmedicine, 2023)
Background The aim of the study was to evaluate the effect of Osgood-Schlatter disease (OSD) on knee joint function in elite young soccer players. Our hypothesis was that knee joint function in elite young soccer players was impaired following OSD compared with soccer players with no history of OSD.